RISK ANTICIPATION OF THE MUDHARABAH FINANCING (CASE STUDY IN THE CIMB NIAGA SYARIAH BANK AT MATARAM BRANCH) - Nurul Susianti (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2021)
This study analyzes the risk anticipation on the mudharabah funding in Nusa Tenggara banks, namely CIMB Niaga Syariah. Unlike the other sharia banks, this bank does not apply mudharabah financing in their services. This analysis uses data collection methods and data analysis techniques using descriptive qualitative research with interview respondents. The respondents were the director of the CIMB Niaga Syariah bank and the direct financing division. Based on the result obtained from interviews and documentation, it shows that the reasons and considerations of the bank not to apply risk anticipation and mudharabah financing are as follows: side streaming, intentional negligence/mistake, and concealment of profits, the funds to be distributed by the bank in the form of mudharabah financing fund from third parties or funds from depositors.